2009
DOI: 10.1029/2008je003094
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for carbonyl sulfide (OCS) conversion to CO in the lower atmosphere of Venus

Abstract: [1] The chemical regimes in the atmosphere of Venus vary from photochemistry in the middle atmosphere to thermal equilibrium chemistry in the lower atmosphere and the surface. Many chemical cycles have been proposed, but few details about these cycles are fully verified by comparison between observations and modeling. Recent high-quality data of carbonyl sulfide (OCS) and CO from ground-based and Venus Express observations provide a unique opportunity to test our understanding of chemistry and transport in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 58 publications
(81 reference statements)
5
55
1
Order By: Relevance
“…This information is highly desirable for better understanding of photochemical processing within Venus' low-latitude mesosphere. For example, the combined HST and JCMT average dayside vertical profile data confirms the altitude dependence inferred from recent photochemical models (Krasnopolsky, 2012;Mills, 1998;Mills and Allen, 2007;Petrass, 2013;Yung et al, 2009) that predict that the SO 2 VMR profile is near constant above $75 ± 10 km, and exponentially decreasing below 75 ± 10 km, assuming that the sulfur chemical processing rates are consistent with that observed on the Earth. At the same time, Zhang et al (2012) and Petrass (2013) show that a small inversion layer (Fig.…”
Section: Insights From the Coordinated Hst/stis Uv + Sub-mm Jcmt Obsesupporting
confidence: 76%
See 1 more Smart Citation
“…This information is highly desirable for better understanding of photochemical processing within Venus' low-latitude mesosphere. For example, the combined HST and JCMT average dayside vertical profile data confirms the altitude dependence inferred from recent photochemical models (Krasnopolsky, 2012;Mills, 1998;Mills and Allen, 2007;Petrass, 2013;Yung et al, 2009) that predict that the SO 2 VMR profile is near constant above $75 ± 10 km, and exponentially decreasing below 75 ± 10 km, assuming that the sulfur chemical processing rates are consistent with that observed on the Earth. At the same time, Zhang et al (2012) and Petrass (2013) show that a small inversion layer (Fig.…”
Section: Insights From the Coordinated Hst/stis Uv + Sub-mm Jcmt Obsesupporting
confidence: 76%
“…Yet, the mechanism(s) that control the exchange of SO 2 between the lower atmosphere and the mesosphere are not fully understood. Some recent modeling efforts have considered whether the vertical transport of the gas to the mesosphere occurs in conjunction with Hadley cell circulation (Yung et al, 2009;Marcq et al, 2013); while previous observers have suggested that direct volcanic ejection (Esposito et al, 1988) may be a key mechanism for the exchange of the gas from the troposphere (z < 60 km) to the mesosphere ($60-90 km, see Clancy et al, 2003;Bertaux et al, 2007). The biggest challenge to understanding how the exchange occurs is the fact that portions of the lower atmospheric region are statically stable.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…However, H 2 S has not been detected in the solid phase (Boogert et al 2000) and instead carbonyl sulphide (OCS) is suggested to be the main reservoir of sulphur on dust grains (Codella et al 2006). OCS has been detected in the condensed phase towards protostar W33A (Gibb et al 2000), within our own Solar system in planetary atmospheres such as Jupiter (Lellouch et al 1995) and Venus (Mills et al 2007;Yung et al 2009) and within cometary comae (Ehrenfreund et al 1997;DelloRusso et al 1998;Bockelee-Morvan et al 2000). Identification of OCS in interstellar ices occurs via the C-O vibrational band ⋆ E-mail: darenburke@hotmail.com at 4.9 μm, which has been shown in the laboratory to be best reproduced by OCS in the presence of methanol-containing ice (Palumbo et al 1995(Palumbo et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Demore, 1982, Hashimoto andAbe, 2001) but the computational expense of the full sulfur cycle, involving multiple species and interactions, limits their use in current Venus General Circulation Models (GCMs). A number of two dimensional (Yung et al, 2009) and three dimensional circulation models (Yamamoto and Tanaka, 1998) have also been used to investigate the microphysics in the Venus cloud. For example Yamamoto and Tanaka (1998) investigated the production of Sulfur Oxides by the catalysis reactions of the sulfur oxides and chlorine oxides(SO x -ClO x ) and suggested that a combination of the Rossby and Kelvin waves are required to reproduce the observed Y shaped structure.…”
Section: Introductionmentioning
confidence: 99%